Annual Plan 2007-08 Volume - II (Sectoral Programmes) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2007)
Andhra Pradesh is the 4th largest State in the country accounting for 8.37% of the country's area and 5th largest in terms of Population The Geographical area of the State is 274.40 lakh H.a that supports a population of 7.62 Crores. It is the largest South Indian State both in terms of population and land area.
Planning Department, Government of Andhra Pradesh